Energy efficiency enhancement in two European data centers through CFD modeling - Onur Muhammed Sarikaya; Mustafa Kuzay; Ender Demirel; Simon Pommerencke Melgaard; Jesper Ellerbaek Nielsen; Rasmus Lund Jensen; Ariel Oleksiak; Wojciech Szeliga (Scientific Reports)
Abstract The new reporting scheme adopted by the European Union focuses on the efficiency assessment of data centers based on key performance indicators (KPIs). This has the potential to lead to further measures for improving energy efficiency of data centers. Consequently, a systematic approach is crucial for assessing and improving data center performance. This study investigates efficiency assessment of two European pilot data centers, located in Denmark and Poland, according to the KPIs calculated through Computational Fluid Dynamics (CFD) simulations of airflow and thermal structures. Two separate experimental approaches were adopted at the pilot sites. One measured airflow and temperatures using external sensors at server inlets and outlets, while the other measured inlet temperatures from embedded server sensors. The good agreement observed between simulated and experimental data confirmed the accuracy of the computational model. The validated CFD model was applied to investigate efficiency improvement opportunities by retrofitting the thermal environment such as rack positioning, containment implementation, and guided airflow control. A series of numerical simulations are performed using the validated numerical model and KPIs are calculated for each design. Numerical simulations demonstrate that the efficiency of an existing data center can be enhanced by up to 75% using the presented approach, although the improvement varied significantly with the specific KPIs. The computational approach proposed here can be readily generalized to guide the efficiency assessment and improvement of existing data centers.